Interaction effect of pollutant degradation and copper transformation in the Cu(II)/PMS system: Overlooked complexation-enhancement role - Jiaxin Miao; Peng Xu; Ruoxi Wu; Lin Deng; Baolin Hou; Jing Zou (Chemical Engineering Journal, 2026)

Unveiling the role of soil in urban vegetation greenness: City-scale evidence from field sampling across green spaces in Shanghai - Hanxin Tang; Mengyao Ci; Quanbo Yu; Shuyi Zhang; Ruoxi Lin; Junjie Ruan; Qicheng Zhong; Min Liu (Journal of Cleaner Production, 2026)

Urban-suburban-rural gradient variations in mortality associated with compound exposure to heat wave and ozone pollution: A case-crossover study using small-area assessment - Kang Ma; Fengman Fang; Xiuya Xing; Yuesheng Lin; Cheng He; Youru Yao; Fei Tong; Jingli Zhu; Huadong Wang; Feiyan Zhang; Ruoxi Li (Journal of Environmental Management, 2026)

piR-16404 drives ferroptotic liver injury via CASTOR1/mTORC1/GPX4 dysregulation in HepG2 cells and mice: a novel toxicity mechanism of N, N-dimethylformamide - Wanli Ma; Xiaoyu Huo; Ruoxi Li; Jingjing Xing; Lin Xu; Dianke Yu (Archives of Toxicology, 2026)

Association of compound exposure to heat wave and ozone pollution with cause-specific cardiopulmonary mortality: A space-time-stratified case-crossover study - Kang Ma; Fengman Fang; Yuesheng Lin; Fei Tong; Cheng He; Youru Yao; Jingli Zhu; Huadong Wang; Xiuya Xing; Feiyan Zhang; Ruoxi Li (Environmental Research, 2025)

Customized decarbonization strategies for central heating in 142 Chinese cities: Combining spatial decomposition with cluster analysis - Guanying Huang; Zhengyu Guo; Ruoxi Xiong; Dezhi Li; Wenshi Lin; Hongzhe Yue (Journal of Cleaner Production, 2025)

City-level Ecological Footprint: Measurement, key determinants, and the role of lifestyle - Ruoxi Zhang; Yuxin Zhang; Yijing Luo; Zixuan Zhang; Lieping Zhen; Zhongjie Lin; Boqian Xu (Energy and Buildings, 2025)

Heterogeneous Fenton-like catalysts of tetranitro iron phthalocyanine@Fe3O4@fly ash composites for fast decomposition of environmental contaminants - Dapeng Li; Peng Zhang; Yang Jin; Qing Li; Xinyuan Li; Ruirui Chang; Ruoxi Ma; Lin Yan; Suxiang Ge; Juntao Ma (Waste Disposal & Sustainable Energy, 2025)
Using fly ash (FA) solid wastes as economical carriers to construct Fenton-like catalytic composites with additional functions is more practical than the use of a single catalyst. Understanding the structure and properties of catalysts and carriers is vital to improve performance. Tetranitro iron phthalocyanine (TNFePc) is a highly active molecular catalyst, whose immobilization and Fenton-like heterogeneous catalysis remain unclear. In this study, magnetically recyclable composites of TNFePc@Fe 3 O 4 @FA were successfully fabricated. Further, Fe 3 O 4 nanocrystals decorated on FA surfaces could be used as special functional layer for composite recycling and simultaneous in situ TNFePc synthesis. Peroxides of H 2 O 2 , KHSO 5 , and tert-butyl hydrogen could be effectively activated by composites and transformed into highly reactive radicals. Moreover, molecular oxygen could be activated as well. Model pollutants, methylene blue and oxytetracycline, could be synergistically degraded by the radical oxidation of superoxide, hydroxyl, alkoxy, and sulfate radicals and non-radical oxidation of high-valent iron-oxo species of TNPcFe IV =O. To the best of our knowledge, this is the first design of FA-based composites with dual function, Fenton-like heterogeneous catalysis and magnetic recyclability, for environmental decontamination. Graphical abstract

Multiple modulating energy-efficient nanofiltration membranes during high-quality drinking water towards high mineral/organic matter selectivity - Xiaozhen Lu; Bin Liu; Xuewu Zhu; Lin Wang; Haiqing Chang; Zhe Yang; Daliang Xu; Ruoxi Wu; Fulin Shao; Jingtao Xu; Heng Liang (Desalination, 2024)

Ultrasmall copper-based nanoplatforms for NIR-II light-triggered photothermal/ photodynamic and amplified nanozyme catalytic therapy of hypoxic tumor - Mengshu Xu; Ruoxi Zhao; Bin Liu; Fang Geng; Xiaodan Wu; Feng Zhang; Ruifang Shen; Huiming Lin; Lili Feng; Piaoping Yang (Chemical Engineering Journal, 2024)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)